Impact of Polypharmacy on Elderly Patients: A Comparative Study of Outcomes and Risk Management - Siddique, Muhammad Irfan (Asian Journal of Pharmaceutics (AJP), 2024)
Polypharmacy is particularly significant in elderly patients because it increases the risk of adverse drug reactions, drug-drug interactions, and medication non-adherence. The purpose of this review paper is to uncover the effect of polypharmacy interventions on the frail elderly patients by comparing the clinical indicators, such as hospitalization, morbidity, and mortality. It also looks at the possible complications including the impact of cognitive impairment, falls, and a decline in quality of life in older adults due to numerous medications. Further, this review presents ideas regarding risk management which include medication reconciliation, deprescribing, and a part of the provider’s duty to monitor and educate patients. The study also brings out the need to develop and implement patient-specific actions to reduce the chances of polypharmacy and enhance the well-being of elderly patients. This paper focuses on reviewing and analyzing various sorts of strategies that have been developed by various healthcare systems in the treatment of elderly patients who have polypharmacy issues to make suggestions that can assist in promoting the safer care of older patients.